Penguatan Kompetensi Sumber Daya Manusia pada Siswa SMA melalui Pelatihan Dasar Kewirausahaan Kreatif dan Financial Literacy di SMA Sedes Sapientiae Semarang - Bonaventura Hendrawan Maranata; Anoki Herdian Dito; Dian Prasetyo Widyaningtyas; Tan, Marcella Wijaya (Pusat Riset dan Inovasi Nasional, 2023)
Sustainable national development requires support from quality, creative, and independent human resources (HR). In facing the challenges of global competition and rapid technological change, strengthening HR competencies since school age is very important. This Community Service (PKM) activity aims to improve understanding and build entrepreneurial character among high school students through basic creative entrepreneurship training. This PKM is carried out by lecturers from the Faculty of Economics, Business and Humanities (FEBHum) of Karangturi National University (UNKARTUR), especially from the Management Study Program, as a form of implementing the Tri Dharma of Higher Education. The activity took place offline at SMA Sedes Sapientiae Semarang on Monday, May 8, 2023, at 09.00–12.00 WIB and was attended by students as participants. This activity presented three speakers who presented material on strengthening HR competencies, the basics of creative entrepreneurship, and financial literacy. The methods used include interactive lectures, group discussions, and question and answer sessions, supported by Microsoft PowerPoint-based presentation media. The results of the activity show an increase in students' understanding of the concept of entrepreneurship, as well as growing interest and motivation to become independent and innovative young entrepreneurs. This activity provides benefits not only for students, but also for schools and universities, in strengthening collaboration in forming superior human resources since secondary education level.